DAKWAH PADA MASYARAKAT MUSLIM MINORITAS: Studi tentang Strategi Dakwah di Masyarakat Muslim Karangasem Bali - Kautsar Wibawa (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
While the obstacles in preaching of Muslim community Karangasem Bali are:The first, the Muslim community at Karangasem of Bali has been a middle to lower economic level then they prefer to work more than follow the activities of da'wah. The secondly, the existence of Muslim communities in Hindu-majority circles, inevitably they have to interact with Hindus, so is not little, Muslims are easily affected by the existing social circumstances. The solution of these barriers are: First, invite the Muslim entrepreneurs to build the economy of the people by making social institutions or Amil Zakat, to be managed and developed for the welfare of the people. Secondly, to invite Muslims don not to be easily influenced by the environment, remain respectful and respectful with Hindus.